Density functional calculation of the electronic circular dichroism spectra of the transition metal complexes [M(phen) 3] 2+ (M = Fe, Ru, Os) - Le Guennic, Boris; Hieringer, Wolfgang; Görling, Andreas; Autschbach, Jochen (Journal of Physical Chemistry A, 2005)
The circular dichroism spectra of the tris-bidentate metal complexes A-[M(phen) ] , with M = Fe, Ru, Os and phen = 1,10-tris-phenanthroline, are investigated computationally, employing time-dependent density functional theory. Good agreement with experimental spectra is obtained for Ru and Os. The A-[Os(phen) ] spectrum is analyzed in detail. It is shown how relativistic effects red shift CD bands where the Os 5d-orbital participates to a large extent in the excitations. Further, the participation of the metal in the ligand π -→ π* exciton CD is determined to be of the order of 10%. Though solvent effects can have a noticeable effect on individual transitions and rotatory strengths, they are demonstrated to have only a very small overall effect on the resulting simulated CD spectra. For A-[Fe(phen) ] , the results are shown to be rather sensitive to the choice of the applied hybrid and nonhybrid density functionals, and the optimized geometries based thereupon. In particular, the sign pattern of the lower-energy part (up to 33 × 103 cm ) of the A-[Fe(phen) ] CD spectrum is difficult to reproduce. Some combinations of functionals and geometries yield good agreement with experiment, but no "best" approach can be devised based on the available results. Possible sources of errors in the spectrum of A-[Fe(phen) ] due to deficiencies in the functionals and the exchange-correlation kernels are investigated. © 2005 American Chemical Society.